The Genome Sequence of Gossypioides kirkii Illustrates a Descending Dysploidy in Plants - Udall, Joshua A.; Long, Evan; Ramaraj, Thiruvarangan; Conover, Justin L.; Yuan, Daojun; Grover, Corrinne E.; Gong, Lei; Arick, Mark A.; Masonbrink, Rick E.; Peterson, Daniel G.; Wendel, Jonathan F. (Frontiers in Plant Science, 2019)
One of the extraordinary aspects of plant genome evolution is variation in chromosome number, particularly that among closely related species. This is exemplified by the cotton genus (Gossypium) and its relatives, where most species and genera have a base chromosome number of 13. The two exceptions are sister genera that have n=12 (the Hawaiian Kokia and the East African and Madagascan Gossypioides). We generated a high-quality genome sequence of Gossypioides kirkii (n=12) using PacBio, Bionano, and Hi-C technologies, and compared this assembly to genome sequences of Kokia (n=12) and Gossypium diploids (n=13). Previous analysis demonstrated that the directionality of their reduced chromosome number was through large structural rearrangements. A series of structural rearrangements were identified comparing the de novo G. kirkii genome sequence to genome sequences of Gossypium, including chromosome fusions and inversions. Genome comparison between G. kirkii and Gossypium suggests that multiple steps are required to generate the extant structural differences.